Profanity In Pulp Fiction - Alif akbar Ramadha; Masrur Yahya; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
This study used Qualitative Content Analysis research as its design. The purpose of this study are: (1) to find out the types of profanity that are uttered in Pulp Fiction; (2) to find out the purposes of the profanity that are uttered in Pulp Fiction. In analysing the data, the researcher used Creswell and Poth’s (2018) qualitative data analysis procedure. The researcher analysed the profanity in Quentin Tarantino’s film Pulp Fiction by using Bergen (2016) and Pinker (2007) profanity theory. The result of this study shows that in Pulp Fiction there are four types of profanity, namely religious, sex, bodily function, and discriminative language. As for the purpose, there are four purpose of profanity in Pulp Fiction, namely dysphemistic, emphatic, idiomatic, cathartic, and abusive. Sex profanity are the most used type of profanity, while religious profanity are the least used type. Emphatic purpose is the most used profanity purpose, while idiomatic purpose are the least used purpose. The suggestion from the researcher were students and teachers should learn profanity as the means to understand and expand their knowledge in profanity language so that students who freely use the words would become more responsible when using profanity. For the next researchers, it would be useful if they investigate profanity based on medias that portray more realistic social interaction or even goes far as focusing on real life human interaction in society